The Role of Micro, Small, and Medium Enterprises in Improving Community Welfare - Audina, Mia; Yunus, Rita; A Parinding, Kalvin; Anwar Nasruddin, M. (Golden Ratio of Data in Summary, 2024)
Efforts to accelerate economic development are one of the government's strategies in empowering the community to reduce unemployment rates, one of which is the existence of Micro, Small and Medium Enterprises (MSMEs) which can improve the welfare of the community, because MSMEs are one of the driving forces for economic growth and development which has a contribution in creating labor and a source of income for the community. This research aims to find out the role of MSMEs in improving community welfare. and What is the government's role in empowering MSMEs in Padende Village. The method used in this research is descriptive with a qualitative approach. Based on research results, it is believed that the role of MSMEs can improve community welfare. This can be reflected in the contribution of MSMEs in meeting family economic needs, providing employment opportunities, and providing people with access to various types of products and services. With the development of MSMEs, local employment opportunities can increase, thereby helping to reduce the unemployment rate in the region. The Government's role in developing MSME sales stalls is able to have a positive impact on MSME players. Organizing entrepreneurship training and development can also help MSME owners improve their abilities in business management, marketing and finance.